In vitro responses of ten indica rice genotypes for callus induction - Repalli, Sai Krishna; Baruah, Ananata M; Das, Prasanta K. (Annals of Agricultural Research, 2018)
Genetic modification approach can supplement crop improvement programs in a long run for nutritional and national food security. Generation of rigid and compact embryogenic callus is an essential and primary step for any kind of transformation and genetic modification in rice. Indica rice varieties are known to be recalcitrant to tissue culture regeneration and choosing a suitable genotype for callus induction has significant importance in rice genetic transformation and regeneration. In this study we had evaluated the callus induction potentials of ten indica rice varieties. Results showed that popular varieties like Swarna (53.3%) and Samba Mahsuri (50%) have highest callus induction frequencies followed by Nagina-22 (40%). Rest of the genotypes showed comparatively less callus induction frequency ranging from (20%-36.6%). There were no significant differences in callus induction efficiency between the replications and the genotypes. Using Duncan’s multiple ranking the ten genotypes were ranked as per the callus induction efficiency for future transformation studies.